A Study on the Challenges of GST E-Filing Faced by the Hotel Industry - Ripleen kaur, Jaspreet Dahiya (Journal of Informatics Education and Research, 2024)
The hotel industry develops to benefit from uniform and even tax rates as well as easy and effective utilization of input tax credit under the Goods and Services Tax. We may anticipate the sector to draw in more international tourists than previously as the ultimate price to end user decreases. This would ideally result in higher government earnings, and the new tax structure has several advantages that might eventually support the growth of industry. For instance, complimentary food (such as breakfast) was previously billed individually under VAT but will now be billed as part of a bundled service under GST. Let's take a closer look at the rates in this sector: